The Effects of The Effects of Empathy on Cyberbullying Mediated by Moral Disengagement on Cyberbullying Mediated by Moral Disengagement (Jurnal Bimbingan Konseling, 2020)
This study was intended to analyze the effect of empathy on cyberbullying mediated by moral disengagement. It involved 310 university students as the sample selected using proportionate stratified random sampling. Their data were collected using Interpersonal Reactivity Index (IRI) scale, Mechanism of Moral Disengagement Scale, and Cyberbullying scale. The results of bootstrapping bias-corrected analysis showed that empathy was negatively predicted by cyberbullying and moral disengagement. Meanwhile, the results of mediation analysis indicated that there was a relationship between empathy and cyberbullying mediated by moral disengagement. Regarding these findings, this study suggests that guidance and counseling service should be aimed at minimizing cyberbullying.